Social isolation of police officers - Vranešević, Milena; Subosic, Dane (Sociološki pregled, 2022)
The theoretical part of the research refers to the analysis of the theoretical material regarding police subculture, with the focus of social isolation of police officers. That is what led to theoretical attitudes, on the basis of which the questions were formulated in the survey questionnaires. Two questionnaires were made, one of which referred to the attitudes of citizens, and the other one to the attitudes of police officers about social isolation of police officers. The total of 100 citizens of Sremska Mitrovica and 100 police officers of the Police Administration in Sremska Mitrovica were surveyed. The research resulted in the confirmed existence of social isolation of police officers, its perception by the citizens and police officers, causes, manifestations, consequences, recommendations and limitations in the application of the reached conclusions.